PERANGKAT PEMBELAJARAN PEDAGOGI ENTREPRENEURSHIP DENGAN PENDEKATAN PEMBELAJARAN BERBASIS PRODUK DI PENDIDIKAN VOKASI - Ganefri Ganefri; Hendra Hidayat; Asmar Yulastri; Aznil Mardin; Diana Sriwahyuni; Ali Akmal Zoni (Universitas Muhammadiyah Semarang, 2018)
This study aims to produce a tool for learning entrepreneurship pedagogy with a product-based learning approach in vocational education. The research model used is the Analysis, Design, Development, Implementation and Evaluations (ADDIE) development model, but is limited to the Design (Development) and Development (validity) stages. Data types are primary data where the data provided by expert lecturers. Data collection instruments in the form of questionnaires and data analysis with descriptive. The results obtainedfrom the study are (1) the design of entrepreneurship pedagogy learning tools with a valid product-based learning approach; (2) The entrepreneurship pedagogy learning tools with the resulting product-based learning approach is formulated in the form of syntax or learning stages for each meeting consisting of: Syntax 1. Formulation of learning outcomes, Syntax 2. Understanding of the concept of lecture material, Syntax 3. Summative evaluation, Syntax 4. Design of project assignments, Syntax 5. Design designs and business products, Syntax6. Product marketing, Syntax 7. Evaluation of project assignment processes and reporting, Syntax 8. Summative evaluation. Based on the findings of this study concluded that the design of entrepreneurship pedagogy learning tools with a product-based learning approach can be used as a learning tool in entrepreneurship courses after carrying out the stages of Implementation and Evaluations so that it is expected to produce entrepreneurship learning pedagogy with a valid, practical and effective product-based learning approach. Keywords: Perangkat Pembelajaran, Pedagogi, Entrepreneurship, Pembelajaran Berbasis Produk